PEMODELAN JUMLAH TINDAK KRIMINALITAS DI PROVINSI JAWA TIMUR DENGAN ANALISIS REGRESI SPATIAL AUTOREGRESSIVE AND MOVING AVERAGE - LISPANI, NI MADE LASTI; SUMARJAYA, I WAYAN; SUKARSA, I KOMANG GDE (E-Jurnal Matematika; Vol 7 No 4 (2018), 2018)
One of spatial regression model is spatial autoregressive and moving average (SARMA) which assumes that there is a spatial effect on dependent variable and error. SARMA can analyze the spatial effect on the higher order. The purpose of this research is to estimate the model of the total crime in East Java along with factors that affect it. The results show that the model can describe total crime in East Java is SARMA(0,1). The factors that influence the total crime  are population density ( ), poverty total ( ), average length of education at every regency/city and error from the neigbors.